The Challenges of Adoption of Circular Economy: Case of China - Rahmani, Mounir (Finance and Business Economies Review, 2022)
China, as a developing country, faces many challenges in resource supply and waste assimilation. Thus, China urgently needed a new model of sustainable development that would be able to overcome the current dilemma and “improve resource productivity and eco-efficiency.” In this case, the circular economy was introduced to help China to enter a more sustainable economic structure. The purpose of this research paper is to present the model adopted by China for the deployment of CE and to present the challenges China faces in order to draw the main lessons for the introduction of CE in Algeria